Do terrorist attacks affect Kenya's financial markets? - Kigen, Dan Kiprono (My University, 2016)
This thesis studied the effects of terrorist attacks on Kenya‟s financial markets between January 2004 and December 2014. The study uses an augmented asset-pricing model similar to that in Eldor and Menelik (2004). The model includes terrorist attack dummies representing location of the attack, the type of attack, the intended target, number of people injured and number of people killed. Data on the terrorist attacks and share index values and foreign exchange rates variables are used to estimate the model. The results show that attacks carried out using explosives had a positive impact on share prices on the NSE. On the flipside, attacks that were carried out on facilities/infrastructure or on religious figures/institutions as well as those carried out using incendiaries had a negative impact on the NSE. An increase in the number of people injured also led to a greater negative impact on the NSE. As regards the forex market, attacks carried out using firearms and incendiaries led to a depreciation of the local currency. Transport attacks on the other hand led to an appreciation. Similarly, the greater the number of people injured led to a greater appreciation of the KES
Thesis submitted in fulfilment of the requirements for the degree of Master of Management in Finance and Investment (MMFI) in the Faculty of Commerce, Law and Management Wits Business school at the University of Witwatersrand, 2016
Keywords: Finance--Kenya; Stock markets--Kenya; Terrorism--Kenya; Kenya--Economic conditions